THE CHARACTERISTIC OF DEEP SEA FORAMINIFERAL COMMUNITY IN TOMINI BAY, SULAWESI - Kresna Tri Dewi; Mustafa Hanafi (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
A total of 14 sediment samples from Tomini Bay, Sulawesi were used for this study as a component of sediment. The samples were carried out by using a gravity corer at water depth range between 600 and 1400 m. This study was a part of mapping activity on marine geology and geophysics during the first cruise of R/V Geomarin III in 2010. The purpose of this study was to examine the subsurface geology related to the potency of energy and mineral resources. Top core sediment samples were washed through 0.063mm opening sieve and then dried in an oven. About maximum 300 foraminiferal specimens were picked from every dried washed residue sample to separate them from other particles under a binocular microscope with brush and water. The result showed that most samples were dominated by planktonic foraminifera (>90%), such as Globorotalia menardii, Orbulina universa, Globigerinoides ruber and others as typical of deep sea sediments. On the other hand, benthic foraminifera was found less than 10% that was represented by Cibicidoides wuellerstorfi, Ceratobulimina pacifica, Pyrgo sp., Bolivinita quadralatera, Uvigerina peregrina, etc. The characteristic of deep sea foraminiferal community of this area may be used for interpreting environmental deposition in the adjacent areas that is useful for petroleum exploration. Keywords: foraminifera, deep sea, Tomini Bay, Sulawesi.